Landsystem analysis of a tropical moraine‐dammed supraglacial lake, Llaca Lake, Cordillera Blanca, Perú - Rodrigo Alberto Narro Pérez (2023)
Tropical glaciers of the Cordillera Blanca, Perú are rapidly thinning and retreating as a result of climate warming. The retreat of these glaciers along narrow linear bedrock valleys has increased the number and size of moraine‐dammed glacial lakes formed in the valleys. This study aims to identify the geomorphological and sedimentological characteristics of an enlarging moraine‐dammed supraglacial lake (Llaca Lake) in the Cordillera Blanca. Field‐based sedimentological observations and geomorphological mapping were combined with remotely sensed data and a photogrammetric model derived from aerial surveys by an uncrewed aerial vehicle to identify landform‐sediment assemblages. The geomorphological and sedimentological characteristics of Llaca Lake are synthesized into three landsystem zones: Zone 1: distal portions of Llaca Lake and the latero‐frontal moraine; Zone 2: the central zone of ice‐cored hummocks; and Zone 3: the active glacier margin. These zones are differentiated based on the spatial distribution of landforms, sediments, and active geomorphological processes. This is the first study to describe the landform‐sediment assemblages in a tropical moraine‐dammed supraglacial lake system and provides a framework for further landsystem element analysis of these growing supraglacial lakes in rapidly deglaciating high‐altitude environments.